The learning outcome approach to European VET policy tools : Where are the arguments and the evidence? - Winch, Christopher [Verfasser] (My University, 2020)
"The principal argument of this paper is that vocational education and training (VET) policy should be free of internal contradictions, be based on sound evidence that it works elsewhere and on good reasons to suppose that it will work in the area of proposed implementation. This argument will be applied to three European VET policy tools, specifically European Qualification Framework (EQF), European Credit System for Vocational Education and Training (ECVET) and European Skills, Competences, Qualifications and Occupations (ESCO) and it will be shown that they fail on all three of these criteria. All three of these tools rely on the flawed learning outcome approach to qualification design. This approach has internal inconsistencies, it can be shown to have failed in other countries and no effort has been made to ascertain whether it could work in the complex world of European VET. Lessons are drawn for future EU policymaking in this area. The paper is a contribution to research into comparative European VET, with a particular emphasis on the challenges of comparing different VET systems and qualifications. The paper thus looks at the rise of the learning outcome approach in England in the l 980s and its application in the Netherlands and South Africa. All the evidence shows that it was a failure. In addition, attention is drawn to inherent design flaws that ensure that it cannot become the basis for qualification design. This is demonstrated in detail through examination of these three policy tools. Of the three, the EQF is the one which still holds some possibilities for development. ECVET could play a limited role if it abandons the learning outcome approach. ESCO is the least promising and consideration should be given to its withdrawal." (author's abstract ; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; T 1.5 International vergleichende Berufsbildungsforschung; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; Vergleichende Berufsbildungsforschung; Berufsbildungssystem; Berufsbildungspolitik; Europäischer Qualifikationsrahmen; Europäisches Leistungspunktesystem; ESCO